Comparison between Single-Dose Esomeprazole- and Pantoprazole-Based Triple Therapy on the Effectiveness for Helicobacter pylori Eradication in Taiwanese Population - Shih, Hsiang-Yao (Hindawi Publishing Corporation, 2012)
Background and Study Aims. To compare the effectiveness of two regimens, single-dose esomeprazole- and pantoprazole-based triple therapy, for Helicobacter pylori (H. pylori) eradication. Patients and Methods. A total of 453 patients were enrolled for H. pylori eradication. They were randomly assigned to either EAC group (Esomeprazole 40 mg once daily, Amoxicillin 1 g twice daily, Clarithromycin 500 mg twice daily for 7 days) or PAC group (Pantoprazole 40 mg twice daily, Amoxicillin 1 g twice daily, Clarithromycin 500 mg twice daily for 7 days). Follow-up endoscopy or urea breath test was scheduled 12–16 weeks after the eradication to evaluate the therapeutic response. Results. Higher eradication rate in EAC group than PAC group was shown by intention-to-treat analysis (EAC 72% versus PAC 55%, P < 0.05) and per-protocol analysis (EAC 91% versus PAC 72%, P < 0.05). The incidence of adverse effects (EAC 19% versus PAC 17%, P = 0.712) and the compliance (EAC 87% versus PAC 91%, P = 0.083) were comparable between these 2 groups. Conclusions. Single-dose esomeprazole-based triple therapy is effective for H. pylori eradication.